PEMANFAATAN LINGKUNGAN SEKOLAH PADA PEMBELAJARAN IPS SISWA KELAS V SD NEGERI 77 PALEMBANG - Eca Haraeti; Muhamad Idris; Puji Ayurachmawati (JS (JURNAL SEKOLAH), 2022)
Abstract : The Utilizitaion Of The School Environment In Social Science Learning Students Of Class V 77 State School Of Palembang. This study aims to determine the results of the use of the school environment as a learning resource in social studies learning by teachers at 77 Palembang Elementary School. The school environment can provide concrete direct experience in social studies learning which contains material on types of economic business. Researchers apply descriptive qualitative research methods. The research instrument obtained from data collection techniques is by conducting field observations or observations, interviews, questionnaires and documentation. Researchers used data analysis techniques (data reduction, data presentation, and drawing conclusions). The results of the research on the environment of the library, school health unit room, canteen and school yard as social studies learning resources obtained a percentage of 80% with good criteria. The conclusion from this research is that the school environment owned by the 77 Palembang State Elementary School as a source of social studies learning is mostly good. Keyword : Social Studies Learning, Social Studies Learning Resources, School Environment Abstrak : Pemanfaatan Lingkungan Sekolah Pada Pembelajaran IPS Siswa Kelas V SD Negeri 77 Palembang. Penelitian ini bertujuan untuk mengetahui hasil dari pemanfaatan lingkungan sekolah sebagai sumber belajar pada pembelajaran IPS oleh guru di Sekolah Dasar Negeri 77 Palembang. Lingkungan sekolah dapat memberikan pengalaman langsung secara konkret dalam pembelajaran IPS yang memuat materi jenis usaha ekonomi. Peneliti menerapkan metode penelitian kualitatif deskriptif. Instrumen penelitian yang diperoleh dari teknik pengumpulan data yakni dengan melakukan pengamatan lapangan atau observasi, wawancara, angket dan dokumentasi. Peneliti menggunakan teknik analisis data berupa (reduksi data, penyajian data, dan penarikan kesimpulan). Hasil dari penelitian lingkungan perpustakaan, ruang unit kesehatan sekolah, kantin dan halaman sekolah sebagai sumber pembelajaran IPS memperoleh persentase sebesar 80% dengan kriteria baik. Simpulan dari penelitian ini ialah lingkungan sekolah yang dimiliki oleh Sekolah Dasar Negeri 77 Palembang sebagai sumber pembelajaran IPS sebagian besar sudah baik. Kata Kunci : Pembelajaran IPS, Sumber Pembelajaran IPS, Lingkungan Sekolah